Records of medical malpractice litigation: A potential indicator of healthcare quality in China - Zhan Wang; Niying Li; Mengsi Jiang; Keith Dear; Chee-Ruey Hsieh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Objective: To assess the characteristics and incidence of medical litigation in China and the potential usefulness of the records of such litigation as an indicator of healthcare quality. Methods: We investigated 13,620 cases of medical malpractice litigation that ended between 2010 and 2015 and were reported to China's Supreme Court. We categorized each case according to location of the court, the year the litigation ended, the medical specialization involved, the severity of the reported injury, the type of allegation raised by the plaintiff - including any alleged shortcomings in the healthcare received - and the outcome of the litigation. Findings: The annual incidence of medical malpractice litigation increased from 75 in 2010 to 6,947 in 2014. Most cases related to general surgery (1,350 litigations), internal medicine (3,500 litigations), obstetrics and gynaecology (1,251 litigations) and orthopaedics (1,283 litigations). Most of the reported injuries were either minor (1,358 injuries) or fatal (4,111 deaths). The most frequent allegation was of lack of consent or notification (1,356 litigations), followed by misdiagnosis (1,172 litigations), delay in treatment (1,145 litigations) and alteration or forgery of medical records (975 litigations). Of the 11,014 plaintiffs with known litigation outcomes, 7,482 (67.9%) received monetary compensation. Conclusion: Over our study period, the incidence of litigation over potential medical malpractice increased in China. As many of the cases related to alleged inadequacies in the quality of healthcare, records of medical malpractice litigation in China may be worth exploring as an indicator of healthcare quality.
Keywords: 330; China; medical litigation; medical malpractice; quality of healthcare